2023
DOI: 10.1002/cai2.60
|View full text |Cite
|
Sign up to set email alerts
|

Advances in medical treatment of advanced hepatobiliary and pancreatic cancer in 2022

Abstract: This article summarizes the drug therapy progress of advanced hepatocellular carcinoma, biliary tract cancer, and pancreatic cancer in 2022, including chemotherapy, molecular targeted therapy, and immunotherapy, to provide reference information for current clinical treatment and future clinical research, and to better improve prognosis and quality of life in patients with hepatobiliary and pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Indeed, precision medicine approaches in cholangiocarcinoma have rapidly expanded in recent years, and pharmacological targeting of FGFR2 fusions ( Goyal et al, 2023 ), IDH1 neomorphic mutants ( Zhu et al, 2021 ), and mutations in kinases including BRAF, HER2 (ERBB2) and NTRK ( Doebele et al, 2020 ; Javle et al, 2021 ; Subbiah et al, 2020 ) have shown clinical promise. Moreover, although initial results with immunotherapy in cholangiocarcinoma were disappointing ( Piha-Paul et al, 2020 ), the combination of immunotherapy with chemotherapy or targeted therapy is showing increased clinical potential ( Oh et al, 2022 ; Zhang et al, 2023 ).…”
Section: Activation Of Notch Signalling As a Driver Of Cholangiocarci...mentioning
confidence: 99%
“…Indeed, precision medicine approaches in cholangiocarcinoma have rapidly expanded in recent years, and pharmacological targeting of FGFR2 fusions ( Goyal et al, 2023 ), IDH1 neomorphic mutants ( Zhu et al, 2021 ), and mutations in kinases including BRAF, HER2 (ERBB2) and NTRK ( Doebele et al, 2020 ; Javle et al, 2021 ; Subbiah et al, 2020 ) have shown clinical promise. Moreover, although initial results with immunotherapy in cholangiocarcinoma were disappointing ( Piha-Paul et al, 2020 ), the combination of immunotherapy with chemotherapy or targeted therapy is showing increased clinical potential ( Oh et al, 2022 ; Zhang et al, 2023 ).…”
Section: Activation Of Notch Signalling As a Driver Of Cholangiocarci...mentioning
confidence: 99%